A record of Bythinella cf. opaca (Gallenstein 1848) (Gastropoda: Prosobranchia: Hydrobiidae) in Bulgaria - Dilian Georgiev; Slaveya Stoycheva (Malacologica Bohemoslovaca, 2008)
Specimens of Bythinella cf. opaca were collected from a stream in Sredna Gora Mts. (West Bulgaria) on 24 Nov 2007 and 17 April 2008. The locality was situated west from village of Djulevo, close to Streltchenska Luda Yana River, UTM-grid: KH80, GPS coordinates: 42 ̊27'15.6" N, 24 ̊20'27.1" E, 393 m a.s.l. We determined the species considering the male genital system structure, but the shell morphology also was looked upon. It was the first record of such species in Bulgaria. After this report the Bulgarian Bythinella species rose to 3: B. austriaca, B. hansboetersi and B. cf. opaca. According to the fact that the species B. austriaca previously recorded in the country was not studied anatomically we consider its occurrence here as not proved.